Presumed ecological speciation in blind mole rats: does soil type influence mate preferences?. Issue 1 (2nd January 2020) - Lövy, Matěj; Šumbera, Radim; Heth, Giora; Nevo, Eviatar
Abstract : Reproductive isolation is a fundamental part of speciation processes. The establishing of reproductive isolation in speciation with ongoing gene flow is unlikely unless divergent selection is overruling gene flow homogenization, which seems to be most effective when combined with non-random mating. We explored whether assortative mating via female mate-choice contributes to reproductive isolation between populations of the blind mole rat Spalax galili inhabiting abutting rendzina-soil and basaltic-soil areas in a microsite similar to one in which ecological speciation has recently been suggested as a possible model driving the divergence between mole rats from the different soils. We performed T-maze experiments with mole rats captured in early winter (i.e. premating season) of 2 consecutive years and found no existence of females from either soil type preferring males originating from their own soils based on olfactory cues. In addition, inconsistent preferences for males based on soil type in tests with females that were tested twice were found. This suggests that female mate choice based on olfactory cues is unlikely to be an isolating barrier between the mole rats from the two soil types. In such circumstances, ecological speciation would have to occur through other mechanisms of divergent selection, such as reproductive isolation due to strong habitat (soil) preferences, vocalisation or seismic communication.